Meningkatkan self management siswa melalui bimbingan kelompok - Lulu Aulia Rahma; Christine Masada Hirashita Tobing; Dewi Purwaningsih (Orien: Cakrawala Ilmiah Mahasiswa, 2023)
the purpose of this study was to improve student self-management through the guidance of student groups at SMP Negeri 243 Jakarta. The method used in this study uses a quantitative approach with a quasi-experimental method. The results of this study indicate that there is an increase in self-management in the posttest given group guidance services. The results of the pretest showed that students who were given services in the low category were 1 student and 39 students in the medium category. While the results of the posttest showed that there were 7 students in the medium category and 33 students in the high category. It can be seen that the experimental class that was given group guidance services could improve student self-management. The data normality test was carried out using the Kolmogrov-Smirnov one-sample test, it was found that the data was normally distributed with a sig value of 0.164 > 0.05. The results of testing the hypothesis through the paired sample t-test can be concluded that group guidance services are effective for improving student self-management.